Aplica??o da NovaGenesis no plano de controle de redes IoT/WSAN centradas ? informa??o, definidas por servi?o e ? agencia espectral - Bontempo, Mar?lia Martins (2019)
the present approach comes up from the necessity of offering network services more suitable to the challenge of the current digital devices and the Internet of Things: sistems that are increasingly heterogeneity, requiring mobility, high bit rates, low latency, data security and others. Therefore, a state-of-the-art research was carried out about the principles that promete performance improvements to standards of the current networks. Network control and management, security, service composition, maming and names resolution, mobility and spectrum management are some of the highlights. As a solution, a system that intends to join the listed network aspects as an alternative tothe complete management of the frequencies spectrum is proposed. It allowns to increase the baud rate of wireless decives that share the same geographic space and the same band, working with different technology standards in an automated way. The proposed system was tested in a real environement of spectrum sharing between IEEE 802.15.4 and IEEE 802.11 networks. The throughput results were measured in several different situations, proving the hypothesis of viability for using the system in evironments of many wireless decives.